Effect of work programme in extension of time entitlement - Idris, Nor Jalilah (2006)
The aim of this research is to know how a construction work programme can be a tool in reducing disputes which relate to extension of time (eot). Extension of time entitlement is only granted to the successful claimant (contractor) who had fulfill certain conditions in the application and one of the condition is the claimant had successfully proved that the delay happened was not by his fault, it is either caused by employer or was one of the neutral events. Therefore it is important for the contractor to have sufficient records and documents about a project’s progress so that he is able to prove the caused of the delay occurred. Unfortunately, most of the contractors failed to do so because they are more focus to the work on site rather than doing the management and documentation work. It is believed then that by having a proper method of work progamme and updated progress of work can be so helpful in resolving the dispute, even the preparation of it are not required in any of local standard form of contract. This research are based on literature information about work programme and it will supported by referring to court case where had considered work programme as an important document in judgment. Even there are no specifications of method in preparing a work programme but there are some important elements in the work programme which may contribute to its purpose. Besides having credits in resolving disputes, there are still weak points in the work programme application which have to be studied and improved. It is found that it is good to have work programme requirement in document contract for the better future and quality of the industry